Silent and Lethal: Consequences of Sexual Violence Against Married Women in Ghana - Apatinga, Gervin A. (Journal of interpersonal violence, 2021)
Extant research, mostly in western countries, confirms the consequences of sexual violence against women, but academic scholarship on this topic remains scant for Ghana. This study built on existing research by exploring the consequences of sexual violence against married women in the Eastern Region of Ghana. Data were obtained from in-depth interviews purposely conducted with 15 survivors of sexual violence. The thematic analysis showed that sexual violence was accompanied by physical and emotional abuse. Following sexual violence and abuse, these women experienced physical injuries, psychological problems, sexual and reproductive health problems, and suicidal ideations. These health difficulties significantly undermined their economic activities and depleted their income. Sexual violence clearly affects women’s empowerment; campaigns against gender-based violence should make sexual violence a top priority in Ghana and elsewhere.